The role of positive goal engagement in increased mental well-being among individuals with chronic non-cancer pain. Issue 4 (November 2019) - Iddon, Joanne E; Taylor, Peter J; Unwin, Jen; Dickson, Joanne M
Individuals with chronic pain commonly report significant functional impairment and reduced quality of life. Despite this, little is known about psychological processes and mechanisms underpinning enhancements in well-being within this population. The study aimed to investigate whether (1) increased levels of pain intensity and interference were associated with lower levels of mental well-being, (2) increased positive goal engagement was associated with higher levels of mental well-being and (3) whether the relationships between pain characteristics and mental well-being were mediated by increased positive goal engagement. A total of 586 individuals with chronic pain participated in the cross-sectional, online study. Participants completed self-report measures to assess pain intensity and interference, mental well-being and goal motivation variables. Results showed that pain interference and positive goal engagement were associated with mental well-being. Moreover, the relationship between pain interference and mental well-being was partially mediated by positive goal engagement. The results provide tentative evidence for the protective role of positive goal engagement in enabling individuals with chronic pain to maintain a sense of mental well-being. The study develops the biopsychosocial model of chronic pain by examining the roles and relationships of relevant yet previously unexplored psychological constructs. The promotion of mental well-being through the enhancement of positive goal engagement is discussed, offering a platform for further research and clinical interventions.